PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PELIBATAN WARGA SEKOLAH TERHADAP IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR NEGERI KECAMATAN NALUMSARI KABUPATEN JEPARA - D. Hapsari Amalia; Nurkolis; Soedjono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The implementation of an independent curriculum is the implementation of an education system that seeks to give freedom to students to think, create, focus on basic material, develop the character profile of Pancasila students, and the required competencies. The implementation of the independent curriculum can run well if the leadership of the school principal can mobilize all potential school resources and the involvement of the school community can involve various educational components to participate in the success of the educational program. The aims of this research are to (1) describe the influence of school principal leadership on the implementation of the independent curriculum; (2) describe the influence of involvement of the school community on the implementation of the independent curriculum; (3) analyze the influence of the principal's leadership and involvement of the school community on the implementation of the independent curriculum in public elementary schools in Nalumsari District, Jepara Regency. The population in this study were state elementary school teachers in Nalumsari District, Jepara Regency, totaling 351 people. After calculating using the Slovin formula, the sample size was 78 people. The sampling technique used proportional random sampling technique. The approach in this research is a quantitative approach with a correlation research type. The data collection method uses questionnaires. Data analysis uses statistical analysis with simple linear regression analysis and multiple regression. The results of the hypothesis test show that (1) there is an influence of the principal's leadership on the implementation of the independent curriculum in the Nalumsari District Public Elementary School, Jepara Regency, with a coefficient of determination of 62.4%; (2) there is an influence of the involvement of the school community on the implementation of the independent curriculum at the Nalumsari District Public Elementary School, Jepara Regency, with a coefficient of determination of 41.5%; (3) there is an influence of the leadership of the school principal and the involvement of the school community together on the implementation of the independent curriculum at the Nalumsari District Public Elementary School, Jepara Regency, with a coefficient of determination of 65.7%. Based on the research results, it is recommended that school principals improve their ability to lead the school community and work together with teachers to encourage collaboration between school members and the community to run smoothly so that the implementation of the independent curriculum can be carried out well.